(untitled) (Iranian Journal of Kidney Diseases, 2015)
Cystinuria, one of the first inborn errors of metabolism, is characterized by hyperexcretion of cystine, arginine, lysine, and ornithine into urine. Cystinuria is genetically classified into types A and B. Mutations in the SLC3A1 gene lead to type A, and type B is caused by mutations in the SLC7A9 gene. We described a 19-year-old woman that had early onset of cystine calculus formation at the age of 3 years. After DNA extraction and polymerase chain reaction, direct sequencing was performed. By these methods, a novel nucleotide substitution c.177G>A in exon 3 of the SLC7A9 gene was found, which had not been reported elsewhere previously. This nucleotide substitution occurs in the extracellular domain of the SLC7A9 gene. In addition, a previously described intron variant c.1136+2/3delT (intron 6 of SLC3A1) in homozygosity status was detected in the patient. To our knowledge, this is the first report of novel nucleotide substitution c.177G>A in exon 3 of the SLC7A9 gene.